The illness representation and treatment adherence of patients with end stage renal disease receiving hemodialysis in Malaysia - Mohd Rasani, Ali Aminuddin; Kritpracha, Charuwan; Thaniwattananon, Ploenpit (Faculty of Nursing, Prince of Songkla University, Hat Yai, Songkhla, 2016)
This study aimed to explore the Illness Representation and Treatment Adherence of patients with end stage renal disease (ESRD) receiving hemodialysis (HD). Ninety patients with ESRD receiving HD were recruited from one public hospital in Kelantan, Malaysia. Questionnaires consisted of three parts: 1) Demographic Data Questionnaire (DDQ), 2) the modified Brief Illness Perception Questionnaire (B-IPQ), and 3) the Treatment Adherence Questionnaire (TAQ). The questionnaires were validated by three experts. The questionnaires were translated from English to Malay language using the back translation technique. The test-retest reliability was tested for the stability of the modified B-IPQ with the result of correlation coefficient of 0.90. The TAQ was tested for internal consistency yielded value of Cronbach’s alpha coefficient of 0.83. The data were analyzed using descriptive statistics and Spearman’s rho correlation statistic. The results revealed that the patients with ESRD receiving HD had the Illness Representation total mean score of 37.02 (SD = 4.17). The analysis also showed that the patients had a median score of 48 (IQR = 6) for the Treatment Adherence. The results also showed that Illness Representation has a negative correlation with Treatment Adherence, which was statistically significant as shown by Spearman’s rho correlation statistic (rs = -0.33, p < 0.01). This study identified the negative correlation between Illness Representation and Treatment Adherence of patients with ESRD receiving HD, implying that patients with more negative Illness Representation were more likely to have difficulty in following their Treatment Adherence. Therefore, it is recommended that an experimental study should be developed and tested the Illness Representation Promoting Program to enhance Treatment Adherence for patients with ESRD receiving HD.